Curriculum Implementation and Innovation in Learning - Muntoha, Ali; Maolana, Firda Nur Alif (Proceedings Series on Social Sciences & Humanities, 2025)
In the face of rapidly changing educational demands, the focus on curriculum implementation and learning innovation has become crucial for schools globally. Conventional curriculum frameworks are no longer adequate to meet the diverse challenges learners face today. Consequently, educators are embracing innovative methods such as competency-based learning, interdisciplinary approaches, and the use of technology including blended learning, gamification, and virtual classrooms to boost student engagement and improve learning outcomes. These innovations create more adaptable, inclusive, and learner-centered environments, helping students develop essential 21st-century skills like digital literacy, critical thinking, and teamwork. Despite these advantages, obstacles remain, such as unequal access to technology, teacher preparedness, and the necessity for continuous professional development. Nonetheless, effective curriculum implementation combined with innovative learning strategies shows strong potential to enhance education quality and prepare students for the demands of the modern digital world.